1973
DOI: 10.2136/sssaj1973.03615995003700010029x
|View full text |Cite
|
Sign up to set email alerts
|

Application of Multispectral Remote Sensing to Soil Survey Research in Southeastern Pennsylvania

Abstract: Computer analyses of multispectral imagery collected from aircraft shows promise for reducing preparation time and increasing the accuracy of soil survey maps. The study area in southeastern Pennsylvania included soils formed from limestone, shale, sandstone, alluvium, and local colluvium. Four study sites ranging in size from 8.5 to 30 ha were selected from a 72 km flightline. Surface reflectance properties of nonvegetated fields were classified using pattern recognition techniques. Computer printout maps sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

1975
1975
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 0 publications
0
3
0
5
Order By: Relevance
“…As curvas espectrais do LV e TRl (Figura 2) mostram que as menores intensidades de reflectância estão associadas ao nível de erosão nulo, e ocorreram entre 650 e 2.450 nm, por apresentarem as amostras de erosão nula maior teor de matéria orgânica (Quadro 2) que absorve mais energia, diminuindo a reflectância entre 400 e 1.200 nm (Mathews et al, 1973) ou em todo o espectro óptico (Courault & Girard, 1988;Madeira Netto, 1996). Para a erosão ligeira, há diminuição do teor de matéria orgânica (Quadro 2) produzindo aumento na intensidade de reflectância (Figura 2), o que também foi observado por Latz et al (1984).…”
Section: Curvas Espectrais E Erosão Do Solounclassified
See 2 more Smart Citations
“…As curvas espectrais do LV e TRl (Figura 2) mostram que as menores intensidades de reflectância estão associadas ao nível de erosão nulo, e ocorreram entre 650 e 2.450 nm, por apresentarem as amostras de erosão nula maior teor de matéria orgânica (Quadro 2) que absorve mais energia, diminuindo a reflectância entre 400 e 1.200 nm (Mathews et al, 1973) ou em todo o espectro óptico (Courault & Girard, 1988;Madeira Netto, 1996). Para a erosão ligeira, há diminuição do teor de matéria orgânica (Quadro 2) produzindo aumento na intensidade de reflectância (Figura 2), o que também foi observado por Latz et al (1984).…”
Section: Curvas Espectrais E Erosão Do Solounclassified
“…Em 1.400 mm soma-se a influência dos grupos OH -, enquanto a banda em 2.200 nm (com formato característico) reflete a presença de caulinita (Mathews et al, 1973). O LV, com Ki na faixa de 1,9 (Quadro 3), apresentou a caulinita como um dos principais minerais de argila, conforme análise de raios-X (Figura 4a).…”
Section: Figura 2 Dados Espectrais Obtidos Com Sensor Terrestre Do Lunclassified
See 1 more Smart Citation
“…The reasons for this are many, but undoubtably include the relatively poor spatial resolution of LANDSAT MSS images, and the inability of present sensors to provide information on subsurface features. However, there is evidence from other countries that multispectral data from sensors aboard aircraft and satellites can provide a useful data source for soil survey, and complement traditional data collection methods (see, for example, Weismiller et al 1977, Mathews et al 1973, Kristof and Zachary 1974 The test areas used in the present study are shown in figure I and include representatives of many of the major soil groups of the British Isles. The present report is restricted largely to data collected from areas C (the 'Winchester test area') and D (the 'Petersfield test area') during the Natural Environment Research Council (NERC) MSS-83 Airborne Thematic Mapper (ATM) campaign.…”
Section: Introductionmentioning
confidence: 99%
“…Romanova (1968) reports that zones of accumulation and deposition of desert sands can be identified by analysis of spectral data and Fischer (1960) suggests that certain rocks may be more easily distinguished on air photographs that record only selected wavelengths of light. Preliminary multispectral studies of soils indicate that computer maps of soils or soil properties can be produced using remote sensing techniques (Al-Abbas et a/., 1972; Baumgardner et al, 1970; Kristoff, 1971 ;Mathews et a/., 1973) but other authors consider these techniques have little application for soil classification and mapping (Frey, 1967) or for identifying rock types (Lyon, 1970).…”
Section: Multiband Signaturesmentioning
confidence: 99%